2017
DOI: 10.1021/acs.jproteome.7b00483
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomic Investigation of Strain Variation in Clinical Mycobacterium tuberculosis Isolates

Abstract: Mycobacterium tuberculosis consists of a large number of different strains that display unique virulence characteristics. Whole-genome sequencing has revealed substantial genetic diversity among clinical M. tuberculosis isolates, and elucidating the phenotypic variation encoded by this genetic diversity will be of the utmost importance to fully understand M. tuberculosis biology and pathogenicity. In this study, we integrated whole-genome sequencing and mass spectrometry (GeLC-MS/MS) to reveal strain-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Two popular applications are proteogenomics approaches (for human and the main model organisms, e.g. (33,34)), and the discovery of novel PTMs (Post-Translational Modifications). Recent reviews in re-use of public proteomics data are available (32,35).…”
Section: Data Re-use Of Public Pride Datasetsmentioning
confidence: 99%
“…Two popular applications are proteogenomics approaches (for human and the main model organisms, e.g. (33,34)), and the discovery of novel PTMs (Post-Translational Modifications). Recent reviews in re-use of public proteomics data are available (32,35).…”
Section: Data Re-use Of Public Pride Datasetsmentioning
confidence: 99%
“…All tandem mass spectra were analyzed using MaxQuant 1.5.5.1 (Cox and Mann, 2008), and searched against a customized M. tuberculosis proteome database. Custom database construction was performed as previously described (Heunis et al, 2017) and are detailed in Supplementary Data Sheet S1. Exploratory data analysis and visualization were performed in the R statistical programming language 1 .…”
Section: Methodsmentioning
confidence: 99%
“…[64] Both in vitro and in vivo, the differences in the profile of pathogenicity and virulence are important factors and, therefore, it is recommended to use different strains for a study to ensure reliable results and accurate prediction of the effect of the compound in a population. [64][65][66] In the present study, compounds 5 b (Lapdesf-20-5b) and 5 n (Lapdesf-20-5n) were identified as the most potent against the resistant strains and, therefore, the most promising. These compounds demonstrated potent activity against all the evaluated strains.…”
Section: Further In-vitro Biological Profiling Of Selected Compoundsmentioning
confidence: 67%